1998
DOI: 10.2466/pms.1998.86.3.1061
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Melatonin May Modulate Glycemic Response to Exercise

Abstract: After a 30-min. standardized bicycle exercise at two times of day in 5 mo. of the year, 62 subjects showed a yearly variation in their glycemic response that was about 5 months out of phase with the peak levels in the light sensitive hormone melatonin, suggesting a reciprocal relationship between melatonin and glucose utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The obvious question is: does complementary lightness during summer nights inhibit melatonin production which then counterbalances a stimulation of melatonin secretion via winter darkness? To arrive at an answer, studies with melatonin measurements in residents at or North of 60N were identified in the peer-reviewed literature: All the empirical investigations (Beck-Friis et al 1984;Martikainen et al 1985;Kauppila et al 1987;Kivelä et al 1988;Levine et al 1994;Stokkan and Reiter 1994;Laakso et al 1994;Weydahl et al 1998;Wetterberg et al 1993Wetterberg et al , 1999aWetterberg et al , 1999b evinced that shorter photoperiods in winter, i.e. decreased ratios between the day's and night's length, may significantly increase yearly averages of melatonin levels in healthy individuals who live at or north of 60N latitude.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…The obvious question is: does complementary lightness during summer nights inhibit melatonin production which then counterbalances a stimulation of melatonin secretion via winter darkness? To arrive at an answer, studies with melatonin measurements in residents at or North of 60N were identified in the peer-reviewed literature: All the empirical investigations (Beck-Friis et al 1984;Martikainen et al 1985;Kauppila et al 1987;Kivelä et al 1988;Levine et al 1994;Stokkan and Reiter 1994;Laakso et al 1994;Weydahl et al 1998;Wetterberg et al 1993Wetterberg et al , 1999aWetterberg et al , 1999b evinced that shorter photoperiods in winter, i.e. decreased ratios between the day's and night's length, may significantly increase yearly averages of melatonin levels in healthy individuals who live at or north of 60N latitude.…”
Section: Epidemiologic Studiesmentioning
confidence: 99%
“…4 The increase in lipid use throughout exercise in melatonin-supplemented rats can be explained by the decrease in carbohydrate use. 5 This event shows that melatonin preserves the glycogen reserves in both the muscles and liver in exercised rats. 5 Studies conducted on pinealectomized rats and rats treated with exogenous melatonin demonstrate that melatonin can regulate the level of insulin and glucagon in blood circulation and the receptor concentration of these hormones in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…5 This event shows that melatonin preserves the glycogen reserves in both the muscles and liver in exercised rats. 5 Studies conducted on pinealectomized rats and rats treated with exogenous melatonin demonstrate that melatonin can regulate the level of insulin and glucagon in blood circulation and the receptor concentration of these hormones in the liver. 6 There are many studies pointing to the relation between melatonin secreted from the pineal gland and 7,8 Zinc is necessary for melatonin synthesis.…”
Section: Introductionmentioning
confidence: 99%